A Correlational Study on Value Added (VA) and Profit with Special Reference to Ultratech Cement LTD - Ashish Premjibhai Chirodiya; S. J. Parmar (Celebes Scholar pg, 2023)
This is a correlational study on Ultratech Cement ltd. The main objective of this study is to find out whether there is any kind of relationship do exist between Value Added (VA) and Profit. Here Value Added (VA) includes Gross Value Added (GVA) and Net Value Added (NVA) only. To find out if there is any relation exist between those variables correlational analysis is used. To fulfil the objective of study, the data of 7 years (from 2015-16 to 2021-22) is taken from the annual reports of the company and analysed by preparing Value Added Statement (VAS). It is found out that there is actually a strong positive correlation exist between Value Added (VA) & Profit (Gross Value Added (GVA) & Profit and Net Value Added (NVA) & Profit).